2007
DOI: 10.1523/jneurosci.4080-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Previous Cocaine Exposure Makes Rats Hypersensitive to Both Delay and Reward Magnitude

Abstract: Animals prefer an immediate over a delayed reward, just as they prefer a large over a small reward. Exposure to psychostimulants causes long-lasting changes in structures critical for this behavior and might disrupt normal time-discounting performance. To test this hypothesis, we exposed rats to cocaine daily for 2 weeks (30 mg/kg, i.p.). Approximately 6 weeks later, we tested them on a variant of a time-discounting task, in which the rats responded to one of two locations to obtain reward while we independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
101
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 41 publications
(56 reference statements)
11
101
2
Order By: Relevance
“…There is accumulating evidence that repeated passive exposure to psychostimulants leads to deficits in tasks that depend on intact prefrontal cortex function (Fletcher et al, 2005(Fletcher et al, , 2007Roesch et al, 2007;Schoenbaum et al, 2004;Schoenbaum and Setlow, 2005). Moreover, withdrawal from repeated passive cocaine or amphetamine treatments also decreases firing rate and bursting activity of dmPFC neurons (Nogueira et al, 2006;Homayoun and Moghaddam, 2007) and abolishes dopamine D 2 receptor-mediated regulation of dmPFC excitability (Nogueira et al, 2006) and membrane bistability of dmPFC neurons (Trantham et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…There is accumulating evidence that repeated passive exposure to psychostimulants leads to deficits in tasks that depend on intact prefrontal cortex function (Fletcher et al, 2005(Fletcher et al, , 2007Roesch et al, 2007;Schoenbaum et al, 2004;Schoenbaum and Setlow, 2005). Moreover, withdrawal from repeated passive cocaine or amphetamine treatments also decreases firing rate and bursting activity of dmPFC neurons (Nogueira et al, 2006;Homayoun and Moghaddam, 2007) and abolishes dopamine D 2 receptor-mediated regulation of dmPFC excitability (Nogueira et al, 2006) and membrane bistability of dmPFC neurons (Trantham et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no published studies have described the effects of chronic AMPH exposure on delay-discounting behavior in an animal model, but several have examined other psychostimulants (Richards et al 1999;Paine et al 2003;Roesch et al 2007;Simon et al 2007;Winstanley et al 2007). While most of these reports suggested that repeated psychostimulant exposure increases impulsive decisions, the most extensive study to date (Winstanley et al 2007) reported no baseline impairments in impulsive choice in rats exposed repeatedly to cocaine (15 mg/kg, i.p., for 21 days).…”
Section: Discussionmentioning
confidence: 99%
“…Although increased impulsivity is considered to be characteristic of individuals who abuse drugs (e.g., Jentsch and Taylor 1999;Coffey et al 2003;Kirby and Petry 2004;Heil et al 2006;Hoffman et al 2006;Verdejo-Garcia et al 2007), there have been relatively few studies that have directly addressed the role of repeated psychostimulant exposure in altering impulsive choice behavior. Those that have (e.g., Richards et al 1999;Paine et al 2003;Roesch et al 2007;Simon et al 2007) suggest that chronic treatment with methamphetamine or cocaine increases impulsivity. However, a recent study by Winstanley et al (2007) showed that repeated cocaine treatment did not alter baseline levels of impulsive choice.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that a high level of impulsivity develops as a result of repeated exposure to abused drugs, and this in turn facilitates the development and/or maintenance of addiction (Jentsch and Taylor, 1999). Evidence supporting this hypothesis comes in part from studies using animal models, where repeated exposure to cocaine in rats leads to an increase in impulsive choice behavior relative to that observed in saline-treated controls (Paine et al, 2003;Roesch et al, 2007;Simon et al, 2007), and from clinical studies, where individuals who have been chronically exposed to cocaine show increases in impulsive choice relative to non-drug users or drug abstainers (for review, see Marsch, 2001 andReynolds, 2006). …”
Section: Introductionmentioning
confidence: 99%